Perlindungan Hukum Bagi Pekerja Di Kota Ambon - Tandjung, Meigy; Salmon, Hendrik; Bakarbessy, Andress Deny (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Sumber Hidup Hospital Ambon, the system of paying wages to its workers is not going well. The Sumber Hidup Hospital Workers' Union filed a lawsuit against Sumber Hidup Hospital at the Ambon District Court.Purposes of the Research: To find out and analyze the wage system based on Government Regulation Number 36 of 2021 Concerning Wages. To find out that companies are required to apply wages based on Government Regulation Number 36 of 2021.Methods of the Research: This research uses normative juridical research methods. The research approach used by the author is a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). The procedure for collecting legal materials is carried out by means of library research. The legal materials used by the author in this study are primary legal materials, secondary legal materials, and tertiary legal materials.Results of the Research: Government Regulation no. 36 of 2021 concerning Wages specifically for Sumber Hidup Hospital workers has not been implemented in practice. particularly in relation to the policy of wages and payment of rights and obligations because there are still many irregularities that occur in the implementation of these Government Regulations. This is evident from the complaints and unrest of the Sumber Hidup Hospital workers where the Sumber Hidup Hospital Foundation as the employer has not paid the workers' wages, so the workers' rights and the employer's obligations have not been fulfilled.